СУВ ХЎЖАЛИГИ ОБЪЕКТЛАРИДА БАХТСИЗ ҲОДИСАЛАР СОДИР БЎЛИШИНИ БАШОРАТ ҚИЛИШ - Ибрагимов, Э.; Газиназарова, С.; Сададдинов, У. (SCIENCE and SOCIETY, 2016)
The article is devoted to the study of methods, used for defining the average number of employees for the predication and analysis of general degree of injuring in the objects of water industry. It also deals with warning actions, providing the labour safety in the objects of water industry.
Keywords: man; safety of vital activity; analysis and prediction of getting injury; the tendency of injuring; dispersion of injuring; method of linear regress; dynamics of injuring